2015
DOI: 10.1128/jvi.02471-14
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Viral Infection of Antigen-Presenting Cells Correlates with the Level of Development of Theiler's Murine Encephalomyelitis Virus-Induced Demyelinating Disease

Abstract: Intracerebral infection with Theiler's murine encephalomyelitis virus (TMEV) induces immune-mediated demyelinating disease in susceptible SJL/J mice but not in resistant C57BL/6 mice. Previous studies have indicated that the major histocompatibility complex (MHC) genes play the most prominent role in the development of TMEV-induced demyelinating disease. In this study, we used C57BL/6.S (B6.S) congenic mice, which carry H-2 s MHC genes instead of H-2 b MHC genes in conjunction with the C57BL/6 (B6) background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…Previous studies have indicated that antigen-presenting cells infected with live TMEV preferentially induce pathogenic Th17 responses, while cells treated with UV-inactivated TMEV or peptide preferentially induce protective Th1 responses [ 13 , 15 ]. Our results in this study indicate that the presence of a high level of initial virus-reactive CD4 + T cells exacerbates the development of TMEV-induced demyelinating disease ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that antigen-presenting cells infected with live TMEV preferentially induce pathogenic Th17 responses, while cells treated with UV-inactivated TMEV or peptide preferentially induce protective Th1 responses [ 13 , 15 ]. Our results in this study indicate that the presence of a high level of initial virus-reactive CD4 + T cells exacerbates the development of TMEV-induced demyelinating disease ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that a higher level of initial viral replication in various antigen presenting cells, including dendritic cells, macrophages, microglia and astrocytes in susceptible SJL mice compared to resistant B6 mice determines the level and type of early T cell responses affecting the protection from or pathogenesis of viral demyelinating disease [ 12 , 15 ]. High levels of viral replication in these antigen presenting cells provide strong innate immunity signaling via TLRs [ 15 , 16 , 17 ] and MDA5 [ 18 ] for the production of various chemokines and cytokines, which, in turn, steer the differentiation of T cell types and modify their effector functions. In addition, activation of the NLRP3 inflammasome and the downstream PGE 2 promote the pathogenesis of TMEV-induced demyelinating disease by enhancing the production of IL-17 [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that some host pattern-recognizing molecules (e.g., TLRs such as TLR7/8 and TLR9) recognize either the viral proteins or nucleic acids encoded by the P2/P3 region and consequently trigger innate cytokine production [ 34 ]. We previously showed that TMEV infection triggers TLR-mediated innate cytokine production in mice via interaction with viral double-stranded RNA (dsRNA) replication intermediates [ 35 37 ]. In addition, we demonstrated that TMEV infection triggers innate immunity in the host via melanoma differentiation-associated 5 (MDA-5) protein [ 38 ], which involves a group of intracellular responders, the retinoic acid-inducible gene I-like receptors (RLR) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetics [2], infectious agents [3], drugs [4], or autoimmune reactions [5] can lead to demyelinating diseases. The basal treatment of demyelinating diseases including using high-dose intravenous methyl-prednisolone [6], immunoglobulin or others [7], but the curative effect varies from person to person.…”
Section: Introductionmentioning
confidence: 99%